A route to obtain Gd2O3:Nd3+ with different particle size - Ferrari, J. L. [UNESP]; Parreira, R. L. T.; Pires, A. M. [UNESP]; Lima, S. A. M. [UNESP]; Davolos, M. R. [UNESP] (Elsevier B.V. Sa, 2011)
This work reports the chemical etching effect of ethylenediaminetetraacetic acid (H(4)EDTA) on the particle size of Gd2O3:Nd3+ phosphor obtained from the thermal decomposition of Gd-2(OH)(2)(CO3)center dot nH(2)O:Nd3+. Thermogravimetric behavior of the precursor Gd-2(OH)(2)(CO3)center dot nH(2)O:Nd3+ (2 at%) is presented and discussed. Structural and spectroscopic investigation of the Gd2O3:Nd3+ powders revealed that this phosphor displays a band emission in the infrared region, which is an important feature for photonic applications. The treatment with different EDTA concentrations results in different Gd2O3:Nd3+ particle size. Through SEM analysis, we have demonstrated that the particle size of Gd2O3:Nd3+ decreases with increasing amount of EDTA. Hereby, we report a chemical etching method as a route to obtain particle size control which is an important requirement to improve phosphor properties and its applicability. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Optical material; Etching; Inorganic compounds